Impact of body mass index in liver transplantation for nonalcoholic fatty liver disease and alcoholic liver disease. Issue 12 (December 2017) - O'Neill, Stephen; Napetti, Sara; Cornateanu, Sorina; Sutherland, Andrew I.; Wigmore, Stephen; Oniscu, Gabriel C.; Adair, Anya
Abstract: Background: This study evaluates long-term outcomes and body mass index (BMI) following liver transplantation (LT) for non-alcoholic fatty liver disease (NAFLD) in comparison with alcoholic liver disease (ALD). Methods: Patient and graft survival were compared using Kaplan Meier curves and log rank test. Multivariable analysis of recipient and donor characteristics was performed as determinants of patient survival. BMI at listing was compared with BMI post-LT. Results: Patient survival at 1-, 3-, 5- and 10 years post-LT was similar in the ALD group (n = 195) compared with the NAFLD group (n = 84) (93% vs. 93%, 91% vs. 89%, 86% vs. 77%, 64% vs. 66% respectively, p = 0.21). One patient in the NAFLD group was re-transplanted and none in the ALD group therefore graft survival was also similar (p = 0.20). Multivariable analysis didn't identify any significant predictors of reduced survival. In comparison with the ALD group, BMI was significantly higher in the NAFLD group at listing (31 vs. 27, p < 0.001), 3-months post-LT (28 vs. 26, p < 0.05) and 6-months post-LT (29 vs. 27, p < 0.05) but was equivalent by 5-years post-LT (29 vs. 30, p = 0.80). Conclusions: NAFLD patients had similar patient and graft survival post-LT compared to ALD. NAFLD patients returned to listing BMI by one-year post-LT but by 5-years post-LT there was no difference in BMI between the groups.